Optimization of Agro-Industrial By-Product-Based Feed as a Substitute for Commercial Feed in Starter Pigs - Pongtuluran, Ardi Matutu; Wiryawan, I Komang G; Salundik; Negara, Windu (Indonesian Journal of Applied Research (IJAR), 2025)
The high feed price, mainly commercial feed, made it unaffordable for smallholder-scale pig farmers in Toraja. As a result, rations were given to pigs without considering nutritional content. This study aimed to substitute commercial feed with agro-industrial by-product-based feed in starter pigs. A total of 20 local breeding pigs, aged 13 weeks, were tested using a randomized group design consisting of 4 treatments with 5 replicates. The treatments were P0 = 100% commercial feed as control; P1 =substitution of 50% with agro-industrial by-product feed; P2 = substitution of 100% agro-industrial by-product feed; P3 = P2 + phytase and mannanase enzymes. ANOVA and Duncan test were performed for analysis the data. The results showed that substituting commercial feed with agro-industrial by-products feed had no negative impact on dry matter (DM), organic matter (OM), and crude protein (CP) intake. However, substituting commercial feed with agro-industry feed significantly decreased the digestibility of feed nutrients. The lowest digestibility values were obtained from the 100% agro-industrial by-product-based feeds at 77.81%, 80.17%, and 38.15% for DM, OM, and neutral detergent fiber (NDF), respectively. Interestingly, adding the enzyme mannanase and phytase (P3) significantly increased the digestibility values of DM, OM, and NDF to 82.79%, 85.14%, and 53.67%. This study also showed no effect of commercial feed substitution up to 50% on the performance of pigs in the starter phase. In addition, this practice can also increase farmers' income by up to 15%.